2022
DOI: 10.1161/str.53.suppl_1.54
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 54: Significantly Higher Odds Of Mortality In Stroke-Related Admissions During COVID-19 Pandemic Versus Pre-COVID/Pandemic: A Meta-Analysis Of 455,073 Stroke Admissions

Abstract: Background: COVID-19, being a prothrombotic state, has been linked to ischemic infarcts. Pooled data on impact of COVID-related stroke on mortality are sparse. We conducted a meta-analysis to assess the risk of stroke-related inpatient mortality (SRIM) during the COVID pandemic vs. pre-pandemic. Methods: Pubmed/Medline, SCOPUS & EMBASE were searched for articles till August 2021 reporting stroke and SRIM during COVID-19 pandemic vs. pre-pandemic. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 54 The largest meta-analysis to date (which included 455,073 stroke admissions), which was recently presented at the International Stroke Conference in 2022, found that patients hospitalized due to stroke during the pandemic had a 42% higher risk of in-hospital mortality compared with those hospitalized during the prepandemic period. 57 …”
Section: The Fact: Reduction In CV Admissionsmentioning
confidence: 99%
“… 54 The largest meta-analysis to date (which included 455,073 stroke admissions), which was recently presented at the International Stroke Conference in 2022, found that patients hospitalized due to stroke during the pandemic had a 42% higher risk of in-hospital mortality compared with those hospitalized during the prepandemic period. 57 …”
Section: The Fact: Reduction In CV Admissionsmentioning
confidence: 99%